Melihat Latar Belakang Australia Dalam Memberikan Bantuan Luar Negeri ke Kawasan Pasifik - Rifaldy, Yusuf (Jurnal Hubungan Internasional, 2020)
Australia is one of the largest foreign assistance donor country to the countries in the Pacific Region. Besides the proximity of geographic location between the two, there are various other factors that cause Australia to provide foreign assistance to the Pacific Region. The Pacific region which consists of small countries and mostly an island nation with a low economic level has a high dependence on foreign aid provided by other countries. This study was conducted to look at Australia’s background in providing foreign assistance to countries in the Pacific Region and what was generated and achieved from the provision of foreign assistance. This study uses literature-based data collection, both using official documents issued by parties related to Australia’s foreign aid issues and other related documents. The results obtained from this study are that Australia provides foreign assistance to countries in the Pacific Region that cannot be separated from Australia’s efforts to obtain its national interests, both in terms of security, economy, and politics.